Responses of seedling growth and survival to post‐germination cotyledon removal: An investigation among seven oak species. (6th March 2019) - Yi, Xianfeng; Bartlow, Andrew W.; Curtis, Rachel; Agosta, Salvatore J.; Steele, Michael A.
Abstract: Rodents regularly rely on emerged epicotyls to locate and remove cotyledons still containing valuable nutrients. However, the extent to which acorn characteristics influence tolerance to post‐germination predation has received little attention. Here, we investigated the impact of cotyledon removal following epicotyl emergence on seedling performance and survival of seven oak ( Quercus ) species. We imitated cotyledon predation at different stages of seedling establishment and development in order to detect effects on seedling height, leaf number and tissue/component mass. Seedling growth and survival were negatively affected by cotyledon loss regardless of oak species. However, these negative effects decreased as the epicotyl length at which cotyledons were removed increased. We also found that there was a threshold epicotyl length above which seedling survival and performance were relatively unaffected in white oak species compared to red oak species. Following cotyledon removal, early germinating white oak (section Quercus ) seedlings survived and/or grew better than the late germinating red oak (section Lobatae ) seedlings. This was likely caused by a difference in dependence on cotyledon reserves, which ultimately affected the ability of seedlings to tolerate cotyledon removal. Synthesis. From an evolutionary perspective, this is likely to follow from the early germination in white oaks and the ability of seed consumers to locate young seedlings from the emerging epicotyls. Our study has implications for forest regeneration by suggesting additional opportunities for white oak species to establish following epicotyl emergence. Future studies should consider quantifying the rates of post‐germination cotyledon loss. Abstract : Following cotyledon removal, early germinating white oak (section Quercus) seedlings survived and/or grew better than the late germinating red oak (section Lobatae) seedlings. This was likely caused by a difference in dependence on cotyledon reserves. From an evolutionary perspective, this is likely to follow from the early germination in white oaks and the ability of seed consumers to locate young seedlings from the emerging epicotyls. Our study has implications for forest regeneration by suggesting additional opportunities for white oak species to establish following epicotyl emergence.